Analisis Hubungan Bauran Pemasaran terhadap Keputusan Pembelian Smartphone Blackberry dan Samsung Android - Alizar Hasan; Yumi Meuthia; Berry Yuliandra; Indah Desfita (Jurnal Optimasi Sistem Industri, 2014)
echnological developments lead to the entire company continues to enhance innovation in creating products derived from it, including the telephone industry.In a few years, the telephone industry introduced a variety of smartphone, including smartphones based on operating system RIM (Research in Motion) which produces branded Blackberry and smartphone based Android operating system with one of the companies that have joined with the operating system is Samsung Android. The research was conducted by measuring the consumer based marketing mix and should be able to explain what factors areas sociated with the sale of the two smartphones. Marketing mixis a set ofmarketing toolsused by companies to continuously achieve their marketing goals. The marketing tools are classified into four groups namely known 4Ps: product, price, place, and promotion. This research was conducted by distributing questionnaires to the respondents as many as 160 pieces and 160 pieces of Blackberry smartphones to the Samsung Android smartphone respondents. Tests performed with Kendall Tau correlation test using SPSS 15 software. The results showed that the variables of product, price and promotion has a significant correlation to the consumer buying decision on Blackberry smartphones. However, variable rates become very dominant variables related to consumer purchasing decisions for Blackberry smartphones. Meanwhile the Kendall Tau correlation test on the Samsung Android smartphones, only products have a price and a significant correlation on consumer purchasing decisions against Samsung's Android smartphones, and variable products become a dominant variables related to consumer purchasing decisions. Thus it can be done by both companies marketing strategies in order to achieve sales targets and products in accordance with marketing objectives.